Quantitative Reduction of Vowels Following Soft Consonants in the Russian Speech of Lithuanians - Balšaitytė, Danutė (Respectus Philologicus, 2012)
This investigation of the acoustic characteristics of phonetic units in the Russian speech of Lithuanians is important for a description of the mechanisms of speech production in a situation of the interference of two languages (native and studied), and for the solution of applied problems of teaching (or correcting) Russian phonetics to Lithuanians.The article analyses the average duration (in milliseconds) of the Russian stressed vowels [i], [e], [a], [u], and their unstressed allophones, when they follow soft consonants in the speech of Lithuanians. The results of the spectral analysis show peculiarities of quantitative reduction of Russian vowels in the speech of Lithuanians, due to the interference of the phonetic systems of the two languages.Four major types of distinctions – in the phonological and phonetic systems of the genetically related Russian and Lithuanian languages, in the degree of quantitative reduction of vowels, in the relation between the duration of different types of unstressed vowels in different positions, and in the relation between the duration of unstressed vowels depending on the placement of the stress – allow deviations from Russian norms of pronunciation to be predicted in the Russian speech of Lithuanians.In unstressed syllables, Lithuanians pronounce vowels of varying duration in place of the graphemes и, е and я, which testifies to the unequal degree of quantitative reduction of these vowels. In Russian, these vowels in unstressed positions are expressed by the same sound and cease to differ. In the pronunciation of Lithuanians, the weak quantitative reduction of the Russian vowel [a] (grapheme я) and the insignificant shortening of the duration of [u] can be observed in all unstressed syllables.According to the received data, in the Russian speech of Lithuanians, a poststressed, non-final vowel can be longer than a vowel in the second prestressed syllable; this breaks the opposition of duration of poststressed vowels to that of all pre-stressed vowels which is characteristic of Russian.
Keywords: phonetic interference; Russian; Lithuanian; quantitative reduction; duration of vowels; normative pronunciation